The Reality of Application of Risk Management in Children Hospital in Benghazi - Faten Salem,; Zainab Hashim,; Noor Alhuda Almahdi,; Hadil Almghrabi,; Marwa Nasib,; Raghda Miftah, (AlQalam Journal of Medical and Applied Sciences, 2024)
Risk management in public hospitals is the process that aims to identify potential risks, evaluate them, and plan to deal with them effectively. This study was intended to explore the reality of application of risk management in Children’s Hospital in Benghazi. Across-sectional descriptive design was used for conducting this study. A total 264 healthcare professionals including doctors, nurses, and administrative staff working in children hospital participated in study. A self-administrated questionnaire was used to collect the data, which included two parts: general information, and risk management. Data were analyzed by SPSS. The results showed that half 51.9% of the participants acknowledged the presence of a dedicated risk management department. Medical risks account for 43.6% of the concerns, and 42% of respondents were unsure if the hospital's management integrates risk assessments into its strategy. Additionally, 63.3% felt that risk forecasting is inadequate, and 72% see the sources of risks as internal and external, and 54.9% believe that there are no effective methods in place to address risks, 58% think that the management does not adopt an effective risk management plan, 65.5% feel that the hospital does not respond to their concerns, 61.7% do not feel secure, and 64% believe that risks are not adequately assessed. The study concluded that presence risk management in children hospital, although it was deemed ineffective. إدارة المخاطر في المستشفيات العامة هي العملية التي تهدف إلى تحديد المخاطر المحتملة، وتقييمها، والتخطيط للتعامل معها بفاعلية. كان الهدف من هذه الدراسة هو تطبيق واقع إدارة المخاطر في مستشفى الأطفال، أجريت دراسة وصفية على 264 من الموظفين داخل المستشفى بما في ذلك الأطباء والممرضات والموظفون الإداريين. تتضمن الأداة المستخدمة في هذه الدراسة استبيانات منظمة، تم جمع البيانات التي تم تحليلها باستخدام SPSS الإصدار 20. تشير النتائج إلى وجود قصور كبير في إدارة المخاطر داخل المؤسسة الصحية. على الرغم من وجود قسم مخصص لإدارة المخاطر بنسبة 51.9%، إلا أنه غير فعال. المخاطر الطبية تمثل 43.6%، و42% من المشاركين غير متأكدين من اعتبار إدارة المستشفى لدراسة المخاطر في استراتيجيتها. كما أن 63.3% يرون أن التنبؤ بالمخاطر غير كاف، و50% أفادوا بتوفر قسم للإبلاغ عن المخاطر. 64% يعتبرون أن الإدارة لا توفر التدريب الكافي للتعامل مع المخاطر، و72% يرون أن مصادر المخاطر تشمل كل من الداخلية والخارجية. 67% يعتقدون أن بيئة العمل تشكل خطرًا، و54.9% يرون عدم وجود طرق لمواجهة المخاطر. 58% يرون أن الإدارة لا تتبنى خطة فعالة، و35.6% لا يلجؤون لقسم إدارة المخاطر عند مواجهة المخاطر. 73.5% يواجهون عراقيل في التعامل مع المخاطر، و65.5% يرون أن المستشفى لا تستجيب لمشاكلهم. 57.6% يرون أن الإجراءات غير مبسطة، و59.8% يعتقدون أن دور إدارة المخاطر ساهم في تحسين الكفاءة. ومع ذلك، 61.7% لا يشعرون بالأمان، و64% يرون أن المخاطر لا تُقيّم بشكل كاف